Functional Genomic Analysis of a RUNX3 Polymorphism Associated With Ankylosing Spondylitis. Issue 6 (2nd May 2021) - Vecellio, Matteo; Chen, Liye; Cohen, Carla J.; Cortes, Adrian; Li, Yan; Bonham, Sarah; Selmi, Carlo; Brown, Matthew A.; Fischer, Roman; Knight, Julian C.; Wordsworth, B. Paul
Abstract : Objective: To investigate the functional consequences of the single‐nucleotide polymorphism rs4648889 in a putative enhancer upstream of the RUNX3 promoter associated with susceptibility to ankylosing spondylitis (AS). Methods: Using nuclear extracts from Jurkat cells and primary human CD8+ T cells, the effects of rs4648889 on allele‐specific transcription factor (TF) binding were investigated by DNA pull‐down assay and quantitative mass spectrometry (qMS), with validation by electrophoretic mobility shift assay (EMSA), Western blotting of the pulled‐down eluates, and chromatin immunoprecipitation (ChIP)–quantitative polymerase chain reaction (qPCR) analysis. Further functional effects were tested by small interfering RNA knockdown of the gene for interferon regulatory factor 5 (IRF5), followed by reverse transcription–qPCR (RT‐qPCR) and enzyme‐linked immunosorbent assay (ELISA) to measure the levels of IFNγ messenger RNA (mRNA) and protein, respectively. Results: In nuclear extracts from CD8+ T cells, results of qMS showed that relative TF binding to the AS‐risk A allele of rs4648889 was increased 3.7‐fold ( P < 0.03) for Ikaros family zinc‐finger protein 3 (IKZF3; Aiolos) and components of the NuRD complex, including chromodomain helicase DNA binding protein 4 (CHD4) (3.6‐fold increase; P < 0.05) and retinoblastoma binding protein 4 (RBBP4) (4.1‐fold increase; P < 0.03). In contrast, IRF5 bound significantly more to the AS‐protective G allele compared to the AS‐risk A allele (fold change 8.2; P = 0.003). Validation with Western blotting, EMSA, and ChIP‐qPCR confirmed the differential allelic binding of IKZF3, CHD4, RBBP4, and IRF5. Silencing of IRF5 in CD8+ T cells increased the levels of IFNγ mRNA as measured by RT‐qPCR ( P = 0.03) and IFNγ protein as measured by ELISA ( P = 0.02). Conclusion: These findings suggest that the association of rs4648889 with AS reflects allele‐specific binding of this enhancer‐like region to certain TFs, including IRF5, IKZF3, and members of the NuRD complex. IRF5 may have crucial influences on the functions of CD8+ lymphocytes, a finding that could reveal new therapeutic targets for the management of AS.